Development of sorption thermal battery for low-grade waste heat recovery and combined cold and heat energy storage. (15th July 2016) - Li, T.X.; Xu, J.X.; Yan, T.; Wang, R.Z.
Abstract: A promising compact sorption thermal battery is developed for low-grade waste heat recovery and combined cold and heat energy storage. Thermal energy is stored in the form of bond energy of sorption potential during the charging phase and the stored thermal energy is released in the form of heat energy and cold energy during the discharging phase. The operating principle and conceptual design of sorption thermal battery based on solid–gas sorption processes is firstly introduced, and then the working performance of sorption thermal battery using consolidated composite sorbent of expanded graphite/manganese chloride is investigated. Experimental verification showed that sorption thermal battery is an effective method to achieve combined deep-freezing cold and heat energy storage, and its working temperature can be easily adjusted by changing system pressure. The cold and heat energy densities are as high as 600 kJ/kg and 1498 kJ/kg, respectively. Moreover, energy densities of different energy storage methods and sorption working pairs are compared and analyzed. It appears that sorption thermal battery is a promising compact high-performance energy storage technology for waste heat recovery and renewable energy utilization due to its distinct advantage of high energy density and broad range of working temperature. Graphical abstract: Heat energy storage density of different solid/liquid-gas sorption working pairs and phase change materials (PCM). Highlights: Sorption thermal battery was proposed for combined cold and heat energy storage. Energy and power densities of sorption thermal battery were studied experimentally. Energy densities of different sorption working pairs were compared and analyzed. Heat energy density from the proposed method is usually higher than 1000 kJ/kg. Sorption thermal battery is very promising for compact high-density energy storage.